Terrathelphusa secula, a new species of semiterrestrial freshwater crab (Crustacea: Brachyura: Gecarcinucidae) from Sabah, East Malaysia, Borneo - Ng, Peter K. L.; Tan, Leo W. H. (Zootaxa, 2015)
A new species of semiterrestrial gecarcinucid freshwater crab, Terrathelphusa secula, is described from Danum Valley in Sabah, East Malaysia, eastern Borneo. In the form of its carapace, third maxilliped, and male second gonopod, it most closely resembles T. ovis Ng, 1997, and T. telur Ng, 1997, from eastern Sarawak and Brunei, respectively. It differs markedly from these and other congeners in its proportionately much wider carapace, and a male first gonopod that is strongly curved and sickle-shaped.